Analysis of Implementation of Entrepreneurship Learning Using Google Meet In Entrepreneurship Class XI Students of SMK Negeri 1 Kutalimbaru - Saut Purba; Akdel Parhusip (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
This study aims to determine (1) the learning process, the use of google meet media in the era of the covid19 pandemic in entrepreneurship subjects in class XI students of SMK Negeri 1 Kutalimbaru, (2) to determine student perceptions about implementing learning with google meet media in entrepreneurship subjects, (3) to find out students' responses to the use of Google Meet media in entrepreneurship subjects. This study uses descriptive qualitative methods, data collection instruments: questionnaires, documentation and observation. The research subjects were class XI students who took entrepreneurship subjects, and teachers who taught entrepreneurship subjects at SMK Negeri 1 Kutalimbaru.The results of this study found that learning using Google Meet media on entrepreneurship subjects was running effectively, this was based on the findings (1) 82.56% of the quality of learning was in the high category, (2) 81.47% of the suitability of learning levels was in the high category, (3) 77.16% of the learning incentives given by the teacher to students are in the sufficient category, and (4) 80.65% or are in the high category for the time of implementation of learning used by the teacher in KBM (teaching and learning activities), the results of observations are also found that teachers tend to have prepared lesson plans (RPP) before learning activities are carried out. Thus, this study found that the use of Google Meet media in teaching and learning activities for entrepreneurship subjects was effective during the Covid 19 pandemic era.